Hoax and Paradox of Digital Public Sphere - Utomo, Wisnu Prasetya (JURNAL KOMUNIKASI INDONESIA, 2022)
Along with technological development, social media have brought various problems which have not been thought of before. Various public conversations are mediated in a space which initially was idealised as an equal and free space. However, multiple indicators indicate that the digital public sphere is vulnerable to hoaxes and fake news. This essay discusses the rise of hoax spreading groups in Indonesia and applied several cases to look back at the public sphere concept in the digital era. Seiring dengan perkembangan teknologi, media sosial telah membawa berbagai masalah yang belum terpikirkan sebelumnya. Berbagai percakapan publik dimediasi di ruang yang awalnya diidealkan sebagai ruang yang setara dan bebas. Namun, beberapa indikator menunjukkan bahwa ruang publik digital rentan terhadap hoaks atau berita palsu. Artikel ini membahas tentang munculnya kelompok penyebaran hoaks di Indonesia dan menerapkan beberapa kasus untuk melihat kembali konsep ruang publik di era digital.